2021
DOI: 10.3390/cimb43010012
|View full text |Cite
|
Sign up to set email alerts
|

Association between Proton Pump Inhibitors and Hearing Impairment: A Nested Case-Control Study

Abstract: This study investigated the association of previous use of proton pump inhibitors (PPIs) with the rate of hearing impairment. The ≥40-year-old population in the Korean National Health Insurance Service-Health Screening Cohort was enrolled. The 6626 registered hearing-impaired patients were matched with 508,240 control participants for age, sex, income, region of residence, and index date (date of hearing impairment diagnosis). The prescription histories of PPIs were collected for 2 years before the index date.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…We gathered the prescription data of each participant for PPIs (lansoprazole, omeprazole, rabeprazole, pantoprazole, ilaprazole, esomeprazole, and dexlansoprazole). The days of PPI use were defined as the total prescription days during the 1 year before the index date [24]. The prescription of PPI was classified as nonuser, current PPI use (prescribed at least once within the previous 30 days), and past PPI use (prescribed at least once within the previous 31-365 days).…”
Section: Exposure (Use Of Ppi)mentioning
confidence: 99%
“…We gathered the prescription data of each participant for PPIs (lansoprazole, omeprazole, rabeprazole, pantoprazole, ilaprazole, esomeprazole, and dexlansoprazole). The days of PPI use were defined as the total prescription days during the 1 year before the index date [24]. The prescription of PPI was classified as nonuser, current PPI use (prescribed at least once within the previous 30 days), and past PPI use (prescribed at least once within the previous 31-365 days).…”
Section: Exposure (Use Of Ppi)mentioning
confidence: 99%
“…The long-term use of PPIs was suggested to accelerate the progression of hearing loss [ 29 ]. In addition, other case-control studies reported a higher risk of hearing loss in PPI users [ 30 , 31 ]. Compared to non-PPI users, PPI users demonstrated a 1.50 times higher risk of hearing loss or tinnitus [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The days of PPI use were de ned as the total prescription days during the 1 year before the index date [24]. The prescription of PPI was classi ed as nonuser, current PPI use (prescribed at least once within the previous 30 days), and past PPI use (prescribed at least once within the previous 31-365 days).…”
Section: Exposure (Use Of Ppi)mentioning
confidence: 99%